A systematic review – Chemical EOR using surfactants and polymers. (2022) - Jain, Shreyansh; Pachisia, Harsh; Sharma, Aman; Patel, Shrey; Patel, Shubham; Ragunathan, Balasubramanian
Abstract: Enhanced Oil Recovery (EOR) techniques can be classified majorly into thermal and non-thermal methods. Thermal methods can be applied to specific field conditions; whereas, non-thermal methods can be applied to a wide range of reservoirs with different conditions. In certain reservoirs where thermal recovery is not possible, Chemical Enhanced Oil Recovery (CEOR) method is applied. The interfacial properties between the reservoir fluids, namely crude oil and formation water, determine the microscopic displacement efficiency of CEOR, specifically for surfactant and/or alkali. The primary benefit from an application of it is to mobilize residual oil saturation by establishing an interfacial tension (IFT) between crude oil and water that is sufficiently low to overcome capillary forces and allow the oil to flow. This paper reviews EOR methods like surfactant and polymer flooding. Subsequently, difference between the uses of the surfactant or polymers according to the favourable reservoir parameters and field conditions. The oil recovery is enriched by either reducing the IFT between the oil–water interfaces using surfactant or by developing a favourable mobility ratio between the displacing water and displaced oil using polymers. Important parameters considered for designing an effective surfactant and polymer formulation design are also studied.